Toward a Four‐Electron Redox Quinone Polymer for High Capacity Lithium Ion Storage. Issue 5 (4th October 2017) - Petronico, Aaron; Bassett, Kimberly L.; Nicolau, Bruno G.; Gewirth, Andrew A.; Nuzzo, Ralph G.
Abstract: Despite recent advances, current polymeric organic cathode materials have failed to incorporate a high degree of lithium storage in a small molecular framework, resulting in low capacities relative to monomers. This report discloses the development of a lithium salt polymer of dihydroxyanthraquinone (LiDHAQS) capable of storing four Li + per monomer. The combination of storing four Li + per monomer and a low molecular weight monomer results in a capacity of 330 mA h g −1, a record for this class of material. The additional redox events responsible for added Li + storage occur between 3.0 and 3.6 V versus Li/Li + resulting in an average discharge potential of 2.5 V versus Li/Li + . These metrics combined yield a high energy density of 825 W h kg −1 which is a 55% improvement over commercial lithium cobalt oxide. The high performance of LiDHAQS makes it a promising material for next generation Li + cathodes. Abstract : A lithium salt polymer of dihydroxyantrhaquinone (LiDHAQS) is synthesized and evaluated as a Li + cathode. LiDHAQS can store 4 Li + in a low molecular weight monomer resulting in a capacity of 330 mA h g –1 . LiDHAQS maintains 80% of its maximum capacity over 370 cycles and has exceptional rate capabilities maintaining 236 mA h g –1 at a 10C rate.